1976
DOI: 10.1002/jrs.1250040409
|View full text |Cite
|
Sign up to set email alerts
|

Lattice vibrations in spectrum of thallous nitrate

Abstract: Raman and infrared spectra of thallous nitrate have been studied in the region 30 to 2000 cm-' for the temperature interval 80 to 460 K. The bands recorded in TlN03 (111) correspond to (v, +Oj) composite transitions where vi refers to internal and Oj to lattice vibrations. There are two sets of nitrate ions in the unit cell because of the observed splitting of the internal bands of the NO; group and also the doubling of some bands due to lattice vibrations.In the vibrational spectra of a crystal with poly-atom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1977
1977
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…Previous studies have shown that the oxalate OCO planes are at some fixed angle to each other. 12,44,55 This results in the observation of multiple bands in the CO stretching region. The infrared spectrum of oxammite also shows bands at 1466, 1447 and 1425 cm -1 .…”
Section: Spectroscopy Of Oxalate Anionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that the oxalate OCO planes are at some fixed angle to each other. 12,44,55 This results in the observation of multiple bands in the CO stretching region. The infrared spectrum of oxammite also shows bands at 1466, 1447 and 1425 cm -1 .…”
Section: Spectroscopy Of Oxalate Anionmentioning
confidence: 99%
“…FT Raman spectroscopy has been used to study urolithiasis disease that has been studied for many years, and the ethiopathogenesis of stone formation is not well understood 41 . Whilst there have been several studies of synthetic metal oxalates 14,21,[42][43][44][45][46] , few studies of natural oxalates have been forthcoming and no comprehensive comparison of the natural oxalates has been undertaken. Few studies of the spectroscopy of water in these minerals have been forthcoming.…”
Section: Introductionmentioning
confidence: 99%
“…Krestov7 has reported an even higher value, 314 J K-1 mol-1, without specifying the source of his data. 75. Dicyanoaurate(I), Au(CN)2-.…”
Section: Pentaatomic Ionsmentioning
confidence: 99%
“…The 70 cm-' frequency observed in the liquid (15-18) has been assigned to the doubly degenerate libration. The 70 cm-' frequency has been observed in the solid phase at liquid nitrogen temperature blue shifted to the region between 73 and 85 cm-' where the librational assignment is much more certain (19)(20)(21). The magnitude of the red shift observed on melting and lattice expansion is reasonable.…”
Section: Discussionmentioning
confidence: 76%